Circ_0088194 Promotes the Invasion and Migration of Rheumatoid Arthritis Fibroblast-Like Synoviocytes via the miR-766-3p/MMP2 Axis - Cai, Yujie; Liang, Renge; Xiao, Shibai; Huang, Qin; Zhu, Dingji; Shi, Guo-Ping; Ouyang, Qingqing; Yang, Min (Frontiers in Immunology, 2021)
Dysregulation of circular RNAs (circRNAs) is involved in various human diseases. Fibroblast-like synoviocytes (FLSs), which form the lining of the joint, are epigenetically imprinted with an aggressive phenotype and contribute to joint destruction in rheumatoid arthritis (RA). In the present study, we identified a novel circRNA, Circ_0088194, which was upregulated in RA fibroblast-like synoviocytes (RA-FLSs) and correlated with the disease activity score in 28 joints. Overexpression of Circ_0088194 promoted RA-FLS migration and invasion, while inhibition of Circ_0088194 had the opposite effect. Mechanistically, Circ_0088194 acted as a miR-766-3p sponge to relieve the repressive effect of miR-766-3p on its target, MMP2 (encoding matrix metalloproteinase 2), thereby promoting migration and invasion. The expression level of Circ_0088194 was inversely correlated with that of miR-766-3p in RA-FLSs. Importantly, overexpression of miR-766-3p partially blocked the migration and invasion induced by Circ_0088194 overexpression. Collectively, this study identified a novel circRNA Circ_0088194 that promotes RA-FLS invasion and migration via the miR-766-3p/MMP2 axis. Circ_0088194 might represent a novel therapeutic target to prevent and treat RA.